1993
DOI: 10.3109/00016349309021111
|View full text |Cite
|
Sign up to set email alerts
|

Iodine deficiency in pregnancy in Denmark

Abstract: Iodine requirements are increased during pregnancy and lactation and adequate iodine intake is important for normal brain development of the fetus/newborn child. The aim of the present study was to evaluate the extent to which this increase in iodine requirement is met in pregnant women living in various regions of Denmark. One hundred and fifty-two healthy pregnant women admitted to five different Danish departments of obstetrics participated in the study. Iodine status was evaluated by measurement of iodine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 8 publications
2
31
1
Order By: Relevance
“…In epidemiological studies the difference in iodine excretion between users and non-users of iodine supplementation is often lower than the difference in intake between users and non-users (Nùhr et al, 1993;Pedersen et al, 1995). The reason for this is not clear.…”
Section: Discussionmentioning
confidence: 91%
“…In epidemiological studies the difference in iodine excretion between users and non-users of iodine supplementation is often lower than the difference in intake between users and non-users (Nùhr et al, 1993;Pedersen et al, 1995). The reason for this is not clear.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have shown that not only pregnant women in iodine-deficient regions 9,10,18 but also those residing in iodine-sufficient areas 7,19 may suffer from iodine deficiency. In the United States, where an effective national programme for dietary iodine supplementation has been in place more than 80 years, the most recent study showed a median urinary iodine level of 145 mg/dl 7 .…”
Section: Discussionmentioning
confidence: 99%
“…This is a cross-sectional study carried out from November 1988 to March 1990 in five different cities in Denmark (14,24,30,31). As the time of study enrollment was before the mandatory Danish iodine fortification of salt introduced in the year 2000 (32), the population had in general mild (East Denmark) to moderate (West Denmark) iodine deficiency with the majority of the women under study living in an area of moderate iodine deficiency (78.6%).…”
Section: Study Design and Study Populationmentioning
confidence: 99%